Self-repairable, recyclable and heat-resistant polyurethane for high-performance automobile tires. (May 2022) - Hu, Shikai; He, Shaoyun; Wang, Yimin; Wu, Yaowen; Shou, Tao; Yin, Dexian; Mu, Guangyao; Zhao, Xiuying; Gao, Yangyang; Liu, Jun; Li, Fanzhu; Guo, Mingming; et al.
Abstract: Tires are widely used in modern society and various industries. However, the formulations and manufacturing processes of traditional rubber are complex, and it is difficult to simultaneously meet requirements of low rolling resistance, high wet-skid resistance and wear resistance. Herein, we demonstrate a polyurethane elastomer material with high heat resistance and self-repairable ability to overcome the challenges encountered during the development of rubber tires. Results show that the polyurethane elastomer based on polycarbonate glycol, 1, 5-naphthalene diisocyanate, and 1, 4-butanediol simultaneously exhibits self-repairable ability, high heat resistance, low rolling resistance, high wear resistance, and high wet-skid resistance. The comprehensive performance of this material matches that of existing green tires. Moreover, the material can be recycled several times. This study is expected to solve the existing problems in rubber tires and provides novel ideas for preparing next-generation high-performance tire materials. Graphical Abstract: ga1 Highlights: A polyurethane elastomer is employed to optimize low rolling resistance, high wet-skid resistance and high wear resistance. The softening temperature of the polyurethane elastomer is 205 °C. The polyurethane elastomer can be recycled several times. The polyurethane elastomer possesses self-repairable ability below softening and degradation temperatures.